One-pot selective production of deoxygenated monomeric, dimeric, and trimeric hydrocarbons from xylose-derived 2-methylfuran using multifunctional tungstate-zirconia-supported Ru, Pd, and Ni catalysts - Jo, Hyeonmin; Choo, Hyunah; Choi, Jae-Wook; Suh, Dong Jin; Yoo, Chun-Jae; Kim, Chang Soo; Kim, Kwang Ho; Lee, Hyunjoo; Kim, Kyeongsu; Choi, Jungkyu; Ha, Jeong-Myeong (Elsevier BV, 2022)
The multifunctionality of tungstate-zirconia-supported metal catalysts was demonstrated in a three-step conversion of 2-methylfuran (2-MF) into deoxygenated C10-15 hydrocarbon fuels in a one-pot reactor, with condensation, hydrogenation, and hydrodeoxygenation performed using single tungstate-zirconia-supported metal catalysts. Manipulation of the reaction conditions, in particular, the reaction temperature and feeding reactant for each reaction step, enabled different catalytic functions of the tungstate-zirconia-supported metals at different reaction stages. Among the metals, Ni favored the production of C-10 hydrocarbons by suppressing further condensation to C-15 compounds, whereas Ru favored the trimerization of 2-MF during the condensation step to produce C-15 hydrocarbons. The superior hydrogenation of 2-MF on Pd reduced the formation of C10-15 compounds. The acidity and hydrogenation activity of the catalysts were investigated to demonstrate the multifunctionality of tungstate-zirconia-supported metals. The catalysts were characterized using H-2 temperature programmed reduction, H-2 temperature programmed desorption, X-ray diffraction, transmission electron microscopy, and nuclear magnetic resonance; the results confirmed the variations in their activity among the different reactions.